Implementasi Teknologi Augmented Reality Sebagai Media Pembelajaran Bahasa Arab Berbasis Android Menggunakan Metode Markerless Tracking - Mochamad Hasyim; Rokhmatulloh; Imron Rosadi; Faizal (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Online learning requires teachers to prepare various media to help the learning process. Learning Arabic at the primary level mainly uses classical methods and uses techniques and media that seem conventional. Researchers tried to minimize this anxiety by utilizing AR technology to make Arabic learning applications more enjoyable, easy to understand, and not boring, especially for elementary school students/madrasah ibtidaiyah. This research aims to implement augmented reality technology with a markerless tracking method to design and build Arabic learning applications on Android smartphones. The research method used in this research is sequential with development progress. This model is a systematic approach and sequence from system planning to the analysis, design, implementation, testing, and maintenance stages. The results of device testing, the application can run perfectly with 1.5 Gb RAM specifications and above and the gingerbread android operating system and above. Testing also goes through 3 black box stages: application functions, marker sensors to the angle of inclination, and the intensity of light needed to bring up the object from the marker. The test shows that the distance parameters, the contrast level of the marker, and the camera tilt angle also affect the output of 3-dimensional objects displayed by the application. In all three stages, the application shows good response and can function as expected.